Experimental investigation of valve driven transient effect in liquid nitrogen pipeline. Issue 1 (1st May 2022) - Bhuvana, R G; Singh Gour, Abhay; Ghosh, Parthasarathi
Abstract: Liquified cryogenic fluids like Liquid oxygen, nitrogen, and hydrogen have various industrial applications. The cryogenic fluid transfer lines are generally fitted with valves to regulate, and control flow. The sudden operations of these valves lead to transient effects characterized by pressure fluctuations. The severity of pressure oscillations depends on various parameters including the valve parameters and the fluid properties. The fluid properties of cryogenic fluid in turn vary rapidly during such valve transients. In this work, a Cryogenic test facility is developed to investigate the valve-driven transients in a liquid nitrogen pipeline. The effect of the transient in the system is evaluated for two different cases of tank pressure and flow rate. The behavior of the transient is detected with the help of dynamic pressure sensors and RTD sensors. Further, the results are interpreted to understand the effect of the transient in the cryogenic fluid transfer system.